2012
DOI: 10.1242/jcs.103119
|View full text |Cite
|
Sign up to set email alerts
|

Brc1-dependent recovery from replication stress

Abstract: Summary BRCT-containing protein 1 (Brc1) is a multi-BRCT (BRCA1 carboxyl terminus) domain protein in Schizosaccharomyces pombe that is required for resistance to chronic replicative stress, but whether this reflects a repair or replication defect is unknown and the subject of this study. We show that brc1D cells are significantly delayed in recovery from replication pausing, though this does not activate a DNA damage checkpoint. DNA repair and recombination protein Rad52 is a homologous recombination protein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 64 publications
(97 reference statements)
6
43
2
Order By: Relevance
“…Similar results were obtained from studies of Brc1, a six-BRCT domain protein (52). ⌬brc1 cells show elevated levels of spontaneous Rad52-YFP foci (53) but reduced spontaneous recombination rates between direct repeats (52). Genetic interaction analysis between ⌬ste20 or ⌬gad8 mutant cells and ⌬brc1 revealed that the double mutant cells are viable but show additive effects with respect to sensitivity to MMS or CPT (Fig.…”
Section: Mutations In Components Of Torc2-gad8supporting
confidence: 72%
See 3 more Smart Citations
“…Similar results were obtained from studies of Brc1, a six-BRCT domain protein (52). ⌬brc1 cells show elevated levels of spontaneous Rad52-YFP foci (53) but reduced spontaneous recombination rates between direct repeats (52). Genetic interaction analysis between ⌬ste20 or ⌬gad8 mutant cells and ⌬brc1 revealed that the double mutant cells are viable but show additive effects with respect to sensitivity to MMS or CPT (Fig.…”
Section: Mutations In Components Of Torc2-gad8supporting
confidence: 72%
“…The presence of Rad52 foci may represent defects in DNA replication (e.g. incompletion of replication, as has been suggested previously (52). The number of Rad52 foci is elevated to very high levels in TORC2-Gad8 mutant cells in response to replication stress (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…[19][20][21] However, a recent study indicated that the requirement for Brc1 more likely involves a role in the resumption of DNA replication at stalled or damaged replication forks. 22 In the case of collapsed replication forks, resumption of DNA replication absolutely depends on homology directed repair. 47 The one-ended DSB formed by the collapsed replication fork invades the sister chromatid to re-establish the replication fork.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%